Futebol brasileiro: a trajetória do jogador de futebol profissional e o fim de sua carreira - Araujo Filho, Wilson Constantino de (2009)
Brazilian soccer: the trajectory of the professional soccer player and the end of its career are the focus of this study, considering that this sport is a relevant instrument in the social life, having collaborated for the consolidation of the Brazilian national identity. The objective was to analyze the career of the professional soccer player from the perspective of the deep changes in the work environment, stressing the formation of the idol figure, through its trajectory and of how the end of the career displays a context marked by the uncertainty of the future and frustrations towards an interrupted dream, where the reclaim of stability presents the dilemma of the acceptance of a new identity inside or out of this sport. It was chosen to use a qualitative methodology, especially the half-structuralized interview, with interlacement of aspects of the theoretical referential and of the interpreting repertoires of the citizens as well. The interview script approached subjects as soccer player career, social ascension, social representation, the relation work/profession, personal evaluation of the career, among others. In order to do so, four former players of professional Brazilian soccer were interviewed, and it was also used as data source news articles propagated in the written press and concerning bibliographies to the considered subject. It was verified that the administration of the sport in Brazil is lead, with rare exceptions, on an amateur way, aiming the interest of few which, supported by statutes and formal and informal rules, perpetuate themselves in powerful positions, harming the professionalization of the administration of this Brazilian sport. It was also verified that the issue of the permanence of this professional in the same segment at the end of its career depends on an anticipated projection, being possible the entrepreneurialism or other formats of insertion in the sport, or even the insertion in another profession accordingly with its academic formation, if there is one